FORMULA DAN UJI ANTIBAKTERI SABUN KERTAS EKSTRAK ETANOL DARI DAUN LIDAH MERTUA (SANSEVIERIA TRIFASCIATA P.) DAN DAUN LIDAH BUAYA (ALOE VERA L.) - Dewi Marlina; Minda Warnis; Fadly Fadly; Ade Agustianingsih; Tedi Tedi (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2022)
Background: The form of soap that has not been widely circulated in the market is soap in sheet form or in paper form. The sheet form will provide an advantage, which is easy to store and can be carried anywhere, and the use of one sheet at a time can maintain the quality of the soap. One of the natural active ingredients that have an antibacterial effect are the leaves of the mother-in-law's tongue leaf plant (Sansevieria trifasciata Prain) and the aloe vera (Aloe vera L.) leaf extract. This study aims to formulate the Ethanol Extract of Aloe Vera Leaf (Sansevieria trifasciata Prain) and Aloe Vera Leaf Ethanol Extract (Aloe vera L.) into paper soap preparations that meet the requirements. Methods: The method used is experimental by making paper soap from mother-in-law's aloe leaf extract and aloe vera extract by making formulas I, II, III with 10%, 15% and 20% percentages of aloe vera extract, while the percentage of aloe vera extract is 3%, 6 % and 9%. And evaluation of the preparation was carried out for 28 days, and Test the effectiveness of Gram positive bacteria (Staphylococcus aureus) and Gram negative bacteria (Escherichia coli). Results: During 28 days of storage, the preparation of soap made from pH-stable paper tends to decrease as well as foam stability and free fatty acid content, but it still meets the requirements of SNI. The results of the organoleptic test of methamphetamine preparations made from paper did not change the smell and color, and did not irritate the skin, And has an inhibitory effect on the growth of Staphylococcus aureus bacteria. Conclusion: Paper soap with ethanol extract of mother-in-law's tongue (Sansevieria trifasciata p.) and ethanolic extract of aloe vera leaf (aloe vera L.) can be formulated into paper-based soap preparations that are stable and meet the specifications required by the Indonesian National Standard (SNI) and are able to inhibit growth. Staphylococcus aureus and Escherichia coli. The most optimal formula in Formula II with varying concentrations of a mixture of 15% aloe vera leaf ethanol extract and 6% aloe vera leaf ethanol extract .